The Circulation of Treatises on Divination and Magic from the 12th to the 17th Century - Rossi, Pietro B. (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2021)
A discussion of Geomancy and Other Forms of Divination edited by Alessandro Palazzo and Irene Zavattero and of La magia naturale tra Medioevo e prima età moderna edited by Lorenzo Bianchi and Antonella Sannino.